Skeletal, dental and profilometric effects of Sabbagh Universal Spring 2 (SUS2) in a patient at the end of growth: A case report - Marchionni, Pierdavide; Di Bari, Roberto; Sferra, Simone; Grippaudo, Cristina (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Introduction: Malocclusions, which present a severe skeletal component, are difficult to solve through orthodontic treatment inpatients at the end of growth and often require a combined orthodontic-surgical treatment. The mandibular propulsion appliances“no compliance” now offer new possibilities for functional orthopedic treatment in borderline cases. Case presentation: A patient at the end of growth with a severe malocclusion (Class II Division 1), open bite with arches’ transversaldiscrepancy, refused the hypothesis of an orthodontic-surgical treatment, which represents the gold standard in such occlusal andskeletal problems, especially in subjects at the end of growth; consequently, a complex orthopedic-orthodontic treatment was chosenas the second choice. The patient has been successfully treated also through the use of SUS2 (Sabbagh Universal Spring 2; Dentaurum,Ispringen, Germany), a “no compliance” fixed functional appliance, wich carried out a significant sagittal correction. Conclusion: The case report especially highlights the important sagittal correction obtained through the use of SUS2. The SUS2 hada functional outcome, which resulted in the maxillary growth stop and an effective sagittal mandibular growth increase. The SUS2effects, enhanced by elastics biomechanics, led to the bite closure and at the achievement of Class I occlusion.